(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
Increasing energy efficiency in industry is crucial for reducing operational costs and promoting sustainability. This abstract provides recommendations for enterprises to implement strategies and measures to improve energy efficiency. These include conducting energy audits, implementing energy management systems, upgrading equipment and systems, optimizing processes, engaging employees through training and awareness programs, participating in demand response programs, integrating renewable energy sources, entering into energy performance contracts, implementing continuous monitoring and maintenance, and benchmarking and sharing best practices. By following these recommendations, enterprises can enhance their energy efficiency, reduce costs, and contribute to a more sustainable future.